‘Communicative sentencing: exploring the perceptions of young offenders in the community’ - Noguera, S (2010)
The purpose of this thesis is to investigate young offenders’ first-hand views of community punishment within the context of the extant literature on communicative theories of sentencing. Fuelled by the traditional marginalisation of young offenders’ views of penal interventions, and drawing upon the qualitative information yielded by fifty semi-structured interviews with 16-18 year old offenders, the study purports to enhance our understanding of the penal messages that punishment communicates to those who experience it. This research initiative is premised on the belief that an empirically-driven research project of this nature can contribute to an improved understanding of the relationship between the youth justice system’s preventive and rehabilitative aims and how offenders themselves perceive the communicative dimensions traditionally attributed to punishment. The Introduction contains the genesis of this investigation and establishes the parameters of the inquiry. Chapter Two analyses the available literature on offenders’ views and argues the case for further research. The third chapter examines the literature on communicative sentencing and anchors the project firmly within the relevant academic debate against which the study’s findings are analysed. Chapter Four contains a detailed account of the methodology employed and prefaces the analysis of findings. While Chapters Five and Six examine the penal messages offenders perceive during sentencing, Chapter Seven explores conceptual issues relating to the communicative functions interviewees ascribed to hard treatment and censure. The next chapter takes cognisance of how offenders conceptualise the penal messages that are transmitted to them during the administration of their sentences. The Conclusion examines the implications of the study’s findings for theory and policy, and proposes a cultural shift from an overly sceptical perspective which does not always afford much value to offenders’ viewpoints, to the creation of a new framework which will allow for greater offender participation.